Hubungan Kecemasan Sosial, Gangguan Makan, dan Penerimaan Diri terhadap Citra Tubuh pada Remaja Putri di SMA Angkasa 2 Halim Perdana Kusuma Jakarta: Relationship between Social Anxiety, Eating Disorders, and Self-Acceptance toward Body Image among Female High School Students at SMA Angkasa 2 Halim Perdana Kusuma, Jakarta - Sumara, Rifa Krisanti; Mulyani, Erry Yudha; Widiastuti, Mariyana; Juliani, Kurnia Dwi; Angela, Nofia; Mulyani, Erry Yudhya; Nofia, Nofia (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Body image is an individual's psychological perception of their body shape, size, and appearance, which can affect self-esteem and is related to an individual's social evaluation, including emotional satisfaction and mental health, especially in adolescent girls. Factors such as social anxiety, eating disorders, and self-acceptance are thought to be related to the formation of body image. The purpose of this study is to investigate the relationship between social anxiety, eating disorders, and self-acceptance on body image in adolescent girls. The research design is quantitative corelasional with a cross-sectional approach. The sample consists of 73 adolescent girls aged 15–19 years selected through purposive sampling and analyzed using the chi-square test. The instruments used were the Social Anxiety Scale for Adolescents/SAS-A questionnaire, the Eating Attitudes Test/EAT-26 questionnaire, the self-acceptance questionnaire, and the MBSRQ-AS questionnaire. The results of respondent characteristics based on age categories showed that 70 respondents (95.9%) were in the mid-adolescent age group (15–17 years), while 3 respondents (4.1%) were in the late-adolescent age group (18–19 years). Statistical tests of the relationship between social anxiety (0.000), eating disorders (0.010), and self-acceptance (0.000) showed a significant association (p<0.05) with body image in adolescent girls. Conclusion: The higher the levels of social anxiety, abnormal eating disorders, and low self-acceptance, the more negative the body image perceived by female adolescents. These findings indicate the importance of psychosocial intervention and nutrition education to improve healthy body perception and prevent eating disorders among female adolescents.